Azathioprine causing cholestatic jaundice in a lupus nephritis patient: A case report and review of literature (Indian Journal of Case Reports, 2019)
The systemic lupus erythematosus (SLE) is an autoimmune disease affecting predominantly females of reproductive age group. Pregnancy is advised only after a period of disease quiescence for at least six months. Azathioprine (AZA) and prednisolone are the immunosuppressants commonly used during pregnancy in lupus nephritis. Azathioprine causing cholestatic jaundice has been reported only a few times but none in a patient with lupus nephritis, pregnant or otherwise to the best of our knowledge. We present an interesting case of a young pregnant patient of lupus nephritis (LN) developing cholestatic jaundice in the third trimester, causing diagnostic dilemma between drug-induced jaundice and Intrahepatic cholestasis of pregnancy which resolved after withholding azathioprine. We should be aware of this uncommon adverse effect of this very commonly used drug in SLE patients.